Abstract Pages: English - Editor (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2015)
Abstract Page for all paper who published on Jurnal Penelitian Pers dan Komunikasi Pembangunan Volume 19 No.1 June 2015